2016
DOI: 10.1016/j.actbio.2015.12.038
|View full text |Cite
|
Sign up to set email alerts
|

On the importance of aging to the crack growth resistance of human enamel

Abstract: With improvements in oral health and an overall increase in quality of life, the percentage of fully or largely dentate seniors is increasing. Understanding the effects of aging on the mechanical properties of teeth is essential to the maintenance of lifelong oral health. In this investigation the effects of aging on the fracture toughness of human enamel were evaluated from incremental crack growth experiments performed on tissue of donor teeth representing “young” (17≤ age ≤ 25) and “old” (age ≥ 55) age grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 54 publications
1
13
0
Order By: Relevance
“…This results in diminished fracture toughness, partly caused by the reduction of organic matrix (Zheng et al, 2013); it also decreases caries susceptibility (Kotsanos and Darling, 1991). In older individuals, cracks are often observed during clinical examination of the enamel surface, alongside enamel crystals (Yahyazadehfar et al, 2016). However, it is not yet possible to prevent the enhancement of enamel brittleness with age.…”
Section: Senescence Of Enamelmentioning
confidence: 99%
“…This results in diminished fracture toughness, partly caused by the reduction of organic matrix (Zheng et al, 2013); it also decreases caries susceptibility (Kotsanos and Darling, 1991). In older individuals, cracks are often observed during clinical examination of the enamel surface, alongside enamel crystals (Yahyazadehfar et al, 2016). However, it is not yet possible to prevent the enhancement of enamel brittleness with age.…”
Section: Senescence Of Enamelmentioning
confidence: 99%
“…Contrary to the crack growth toughening observed in young enamel (Fig. 5A), the process is negligible in old enamel [81]. This finding provides further evidence of why cracks are more frequently identified in the surfaces of teeth of seniors.…”
Section: Agingmentioning
confidence: 50%
“…A comparison of the fracture toughness in two directions of cuspal enamel from the teeth of young (age ≤ 25) and old (55 ≤ age) donor teeth are shown in Fig. 5B [81]. For the longitudinal direction, the fracture toughness decreased by approximately 35% over the age span from the young and old groups.…”
Section: Agingmentioning
confidence: 99%
“…Aside from scalloping, microcracks faced curvatures, bridging, and bifurcations [ 1 ]; there was a tendency for the width of the gap between its edges to change within the same pathway in all groups ( Figure 3 ). Two studies [ 21 , 24 ] found that crack deflection and bifurcation were more prominent as anticrack defense mechanisms than the bridging mechanism in enamel of more than 50 years of age. Unfortunately this was not an objective in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanical and compositional differences between adult teeth and deciduous teeth have been discussed [ 6 , 7 , 17 , 27 ], none compared the enamel of immature premolars to mature premolars. One study on third molars showed that enamel became less resistant to fracture with increasing age (17–25 years of age versus ≥55 years of age) [ 24 ]. Our findings indicate that enamel becomes more resistant against microcracking with time at younger age groups (from adolescence to 30 years).…”
Section: Discussionmentioning
confidence: 99%